2009
DOI: 10.1208/s12248-008-9078-8
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Liposomal Formulation for Sustained Delivery of Colchicine: In Vitro Characterization and In Vivo Evaluation of Anti-gout Activity

Abstract: Abstract. Colchicine, an alkaloid found in extracts of the plants Colchicum autumnale and Gloriosa superb, is effective in the treatment of acute gout and dermatological conditions like leuko-cytoclastic vasculitis, psoriasis, and Sweet's syndrome. Oral administration of colchicine is associated with gastrointestinal side effects and its accumulation in the body leads to bone marrow suppression. In the present study, an attempt has been made for development and in vitro and in vivo evaluation of elastic liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…The results revealed that after storage in the absence of sunlight for 6 months, the percentages of the remaining curcumin, bisdemethoxycurcumin and demethoxycurcumin were 91,96 and 88, respectively [104] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 99%
“…The results revealed that after storage in the absence of sunlight for 6 months, the percentages of the remaining curcumin, bisdemethoxycurcumin and demethoxycurcumin were 91,96 and 88, respectively [104] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 99%
“…It has been suggested that topical administration of colchicine could be beneˆcial in the treatment of gout and other dermatological conditions along with increase in its sitespeciˆcity. In our previous study, we prepared a colchicine elastic liposomal formulation and found 8-fold enhancement in skin deposition and 4-fold increase in biological anti-gout activity as evaluated by Mono sodium urate (MSU)-induced arthritis model 8) in comparison with colchicine solution in PBS. In this study an attempt was made to prepare b cyclodextrincolchicine complex and to study its eŠect on in vitro skin permeation and deposition and biological antigout activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the quantity needed of phospholipids and surfactants (as EAs) is essential to organize a thin film [50,51]. ​ It is largely worn for the research of multilamellar vesicles.…”
Section: Methods Of Preparationmentioning
confidence: 99%